2017
DOI: 10.1038/cddis.2017.453
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose ameliorates oxidative stress-mediated mitochondrial dysfunction and ER stress via selective autophagy stimulation and autophagic flux restoration in osteoarthritis development

Abstract: Oxidative stress-related apoptosis and autophagy play crucial roles in the development of osteoarthritis (OA), a progressive cartilage degenerative disease with multifactorial etiologies. Here, we determined autophagic flux changes and apoptosis in human OA and tert-Butyl hydroperoxide (TBHP)-treated chondrocytes. In addition, we explored the potential protective effects of trehalose, a novel Mammalian Target of Rapamycin (mTOR)-independent autophagic inducer, in TBHP-treated mouse chondrocytes and a destabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 56 publications
6
112
0
Order By: Relevance
“…To our knowledge, the expression alteration of p62 (a protein representing the degradation level of autophagic vacuoles) and lysosome activity in the process of IVDD is still unknown. Our group latterly reported that high accumulation of p62 appears in human OA cartilage and destabilized medial meniscus (DMM) mouse OA model, suggesting that autophagic degradation is blocked in OA chondrocytes 39 . Moreover, Kim et al observed accumulation of lysosomes and decline of lysosomal activity in human OA chondrocytes relative to normal chondrocytes, also they showed that destroying lysosome results in enhanced chondrocyte apoptosis and inhibition of autophagy 40 .…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, the expression alteration of p62 (a protein representing the degradation level of autophagic vacuoles) and lysosome activity in the process of IVDD is still unknown. Our group latterly reported that high accumulation of p62 appears in human OA cartilage and destabilized medial meniscus (DMM) mouse OA model, suggesting that autophagic degradation is blocked in OA chondrocytes 39 . Moreover, Kim et al observed accumulation of lysosomes and decline of lysosomal activity in human OA chondrocytes relative to normal chondrocytes, also they showed that destroying lysosome results in enhanced chondrocyte apoptosis and inhibition of autophagy 40 .…”
Section: Discussionmentioning
confidence: 97%
“…For immunofluorescence, as a previous study described, EPCs were plated in six‐well glass plates, and then, after incubating with serum‐starved medium overnight, the cells were treated with 50 μM TBHP or were co‐treated with 50 μM TBHP and 1 μM melatonin for 2 hours in medium. The cells were washed three times with PBS before fixation using 4% paraformaldehyde, followed by permeation using 0.5% Triton X‐100 for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we applied tert‐butyl hydroperoxide (TBHP), which is commonly used as an exogenous inducer of oxidative stress, to establish a pathological IDD condition in primary EPCs in vitro. We investigated the effects of melatonin on apoptosis and calcification in EPCs under oxidative stress and illustrated the possible mechanism of melatonin in ameliorating IDD processes.…”
Section: Introductionmentioning
confidence: 99%
“…47) Recently, Cetrullo et al demonstrated that autophagic flux was impaired by excessive oxidative stress in human chondrocytes. 48) In t-butyl hydroperoxide-treated-chondrocytes, trehalose attenuated apoptosis through restoration of autophagic flux via increased LC3-II and decreased p62 protein expression. 49) p62 acts as a cargo receptor for autophagic degradation and is a target gene for transcription factor, nuclear factor-E2-related factor 2 (Nrf2) creating a positive feedback loop by inducing antioxidant response element-driven gene transcription.…”
Section: Discussionmentioning
confidence: 99%